THE The Relationship Of Achievement Motivation And Transformational Of Leadership Style With Public Organizational Performance - Usman Effendi (Jurnal Sociohumaniora Kodepena (JSK), 2023)
This study determines the relationship between achievement motivation and transformational leadership style with public performance. The object of this research is the state civil apparatus with an unlimited population who work for Indonesian Government Ministries and Institutions located in the city of Jakarta and its surroundings. The research method uses descriptive quantitative research, namely the analysis technique using multiple linear regression. Aims to describe and explain the characteristics of a situation at a certain time in order to summarize the relationship that occurs between achievement motivation and transformational leadership style with performing public organizations. While the number of samples taken by convenience was as many as 70 participants with data collection using a Likert scale. The results showed that there was a relationship between achievement motivation and performing public organizations with a value of (r) = 0.366. And there is a relationship between transformational leadership style and performing public organizations with a value of (r) = 0.286. Then achievement motivation and transformational leadership style with the performance of public organizations with a value of (R2) = 0.136, this shows that there is a simultaneous relationship.